1978
DOI: 10.1159/000172654
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propranolol on Sodium Reabsorption and the Renal Circulation

Abstract: The effects of intrarenal arterial (6.5 µg/kg/min) and intravenous (33 µg/kg/min) administration of propranolol on sodium excretion and renal hemodynamics were studied in anesthetized dogs. Heart rate, plasma renin activity and renal plasma flow were reduced by propranolol administered by either route. Blood pressure was reduced following intravenous infusion. Urinary sodium excretion was reduced by propranolol. This reduction was inversely correlated with the basal state of sodium excretion, and was also corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Furthermore, acute administration of propran olol is reported not to change urinary sodium excretion [3] or even to induce an antinatriuretic effect in dogs [11], an increase in Na* excretion having been reported only in rats [12], In agreement with the animal find ings, intravenous administration of propranolol in man resulted in a decrease in renal plasma flow [13]. More generally, a deterioration in renal hemodynamics is at tributed to (3-blocker administration in man [2], with the exception of nadolol, for which an increase of renal plasma flow has been observed in animals and in man [3,4], The reduction of cardiac output is partly responsible for the decrease in renal hemodynamics associated with [3-blockers.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, acute administration of propran olol is reported not to change urinary sodium excretion [3] or even to induce an antinatriuretic effect in dogs [11], an increase in Na* excretion having been reported only in rats [12], In agreement with the animal find ings, intravenous administration of propranolol in man resulted in a decrease in renal plasma flow [13]. More generally, a deterioration in renal hemodynamics is at tributed to (3-blocker administration in man [2], with the exception of nadolol, for which an increase of renal plasma flow has been observed in animals and in man [3,4], The reduction of cardiac output is partly responsible for the decrease in renal hemodynamics associated with [3-blockers.…”
Section: Discussionmentioning
confidence: 97%
“…This has been explained by the initiation of a reflex peripheral vasoconstriction (mediated by the sympathetic nervous system) in response to a reduced cardiac output following acute administration of these agents (Scriabine, 1979;Conway, 1980). In addition to their cardiac effects, some P-adrenoceptor blocking agents have been reported to reduce both renal blood flow and function, after acute administration, in both animals (Nies et al, 1971;Abdel-Razzak, 1977;Nomura et al, 1978) and man (Zech et al, 1975;Sullivan et al, 1976;Wilkinson, 1982). This renovascular effect may be a contributory factor in the increased vascular resistance seen with these agents.…”
Section: Discussionmentioning
confidence: 99%
“…The most consistent effects of a P-adrenoceptor blocking agent are to reduce cardiac output and heart rate (Nies et al, 1973;Garvey & Ram, 1975;Burden & Hamilton, 1976;Buckingham & Hamilton, 1980;Cohn, 1983). Although P-adrenoceptor blockade is not generally noted for any effects on renal function, it has been reported that P-adrenoceptor blocking agents can impair renal function, possibly through a reduction in renal blood flow, and an increase in Na'reabsorption (Nies et al, 1971;1973;Abdel-Razzak, 1977; Nomura et al, 1978). Clearly, the cardiac and renovascular responses to an ACE-inhibitor differ from those to a P-adrenoceptor blocking agent.…”
Section: Introductionmentioning
confidence: 99%